Design and prototyping of a shoot-them-up game - Liu, Huaping (2015)
A Shoot-Them-Up game is a sub-genre of the shooter game. In a Shoot-Them-Up game, a player controls a flying object (usually a spaceship or aircraft) and destroys waves of enemies while dodging their attacks. Shoot-Them-Up games call for fast reactions and for the player to memorize levels and enemy attack patterns to confront overwhelming numbers of enemy projectiles. Research has revealed that fast-paced action games such as Shoot-them-up help to train the player into faster and better decision-makers and increase their hand-eye co- ordination. The target players of the game are teenagers and elderlies. This project aims to design and prototype a Shoot-Them-Up game. The game development involves building a user-friendly interface with functions for a player to change game settings, select campaigns and change difficulty levels for each campaign. Furthermore, it allows developer to create new campaign to the game in few steps and allows the game to implement in multiple platforms. Unity was used for the development and the programming language used was C#. This report presents the evaluation results of the given project, comparison results of existing 4 mobile versions of Shoot-Them-Up games and lastly, describes the process of designing and implementing the prototype game.